“Senggol Bestie” as Media Promotion Among Muhammadiyah Universities - Dani Fadillah; Muhammad Najih Farihanto; Resdika Anggesa Dwi Setiawan (Universitas Muhammadiyah Yogyakarta, 2022)
This paper aims to discuss the emergence of the phenomenon of mutual flexing carried out by Muhammadiyah universities on TikTok social media. So far, every business entity that carries out promotions for its agency tends to avoid offending other agencies and only focuses on discussing the advantages of its products, even if it has to touch other institutions. This has never been done openly. This research was conducted using a qualitative approach with phenomenological analysis. The author collected data with participant observation to find out the participants’ essential phenomena in their life experiences. In this case, the author managed the content of official social media creators of Muhammadiyah Universities who created TikTok publication content. Then based on the data obtained from the resource persons, the author draws a research conclusion. The conclusion of this study shows that flexing activities carried out by content creators of Muhammadiyah Universities have the potential to become a new form of publication style that has never existed before among universities.